A closer look: obsessive-compulsive symptoms among intern nurses amidst COVID-19 pandemic - Mona Metwally El-Sayed; Eman Sameh Abd Elhay; Manal Mohammed Hawash; Hassan Mohammed Sonbol; Samah Mohamed Taha (BMC, 2024)
Abstract Background The distinctive circumstances and socio-cultural context in Egypt make it crucial to explore the psychological well-being of intern nurses amid the COVID-19 pandemic, with a specific focus on obsessive-compulsive symptoms. This study aimed to investigate the influence of fear of COVID-19 on obsessive-compulsive symptoms among intern nurses. Methods A cross-sectional survey involving 375 randomly recruited intern nurses was conducted. Data collected included the Fear of COVID-19 Scale and the Short Version of the Arabic Obsessive-Compulsive Scale. Results A significant relationship was found between the fear of COVID-19 and the severity of obsessive-compulsive symptoms among the participants (r = 0.472, p = 0.000). A stepwise regression analysis indicated that the fear of COVID-19, living in urban regions, frequency of COVID-19 infection, and increased number of infected family members may contribute to the severity of Obsessive-Compulsive Symptoms with adjusted R2 value = 27.5%. Conclusion The findings suggest that the COVID-19 pandemic has had significant psychological impacts on newly qualified nurses during their internship training period, including the manifestation of mental health symptoms such as Obsessive-Compulsive Symptoms. It was observed that urban residents, intern nurses with recurrent COVID-19 infections, and those with more infected family members exhibited a higher severity of OCS. These findings underscore the need for further research to investigate additional factors that may influence OCS severity.